Scapulothoracic dissociation: a devastating “floating shoulder” injury - Branca Vergano, Luigi; Monesi, Mauro (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work The term “floating shoulder” was used in a previous paper to describe lesions of at least two components of the SSSC (superior shoulder suspensory complex), a bony-ligamentous structure of the shoulder girdle. Following this article other types of floating shoulder were described, including scapulothoracic dissociation (STD), a rare lesion with potentially devastating consequences, with detachment of the scapular body from the thoracic wall, with following lateralization of the scapula, fracture of the clavicle or injury of the adiacent sterno-clavear or acromion-clavicular joints. Prognosis and outcome are also negatively influenced by secondary vascular and neurologic injuries. Methods We review the literature on this lesion and we describe two patients with STD, their treatment and outcome. Results Reviewing the literature and analysing our cases, we point out that the STD is often associated with serious general lesions and is indicative of an high-energy trauma. The consequences can be disabling for the upper limb (20% amputation, 50% flail limb) or for the general status of the patient (10% mortality). Conclusions STD must be timely recognized and subsequently properly treated, to avoid the associated general and local injuries (vascular) and subsequently the musculoskeletal lesions.